Caractérisation phénotypique des entérobactéries isolées d’infection urinaire : Résistance aux antibiotiques et capacité de formation du Biofilm - Brahmia Souha; Bendjedid Nour (My University, 2026)
Abstract: Between December 2025 and May 2026, a study was conducted at the Ibn Rochd Public Hospital in Souk Ahras, Algeria, to analyze the epidemiological and bacteriological profile of urinary tract infections, characterize the antibiotic resistance of isolated Enterobacteriaceae, and assess their ability to form a biofilm. Of 200 urine cultures, the prevalence of confirmed urinary tract infections was 15.5%, with a female predominance (56%) and a majority of hospitalized patients (75%). Enterobacteriaceae represented 74% of the isolates, dominated by Escherichia coli (38.7%) and Klebsiella pneumoniae (29%). The antibiogram (VITEK 2) showed high resistance rates: ampicillin 100%, cefotaxime 87%, and amoxicillin-clavulanic acid and ciprofloxacin approximately 80%. Resistance phenotypes revealed 33% ESBLproducing strains and 40% carbapenemases, including five metallo-beta-lactamases (MBLs). Biofilm formation (Crystal violet) was variable, with a significant association between urinary catheterization and strong biofilm (p = 0.007), but no correlation with resistance or carbapenemases. These results confirm the urgent need to strengthen surveillance, rationalize antibiotic therapy, and develop anti-biofilm strategies. -------------------------------------------------------------------------------------------------------------------------------------------------------- في الفترة ما بين ديسمبر 2025 ومايو 2026، تم إجراء دراسة في مؤسسة المستشفى العمومي ابن رشد في سوق أهراس (الجزائر) لتحليل المظهر الوبائي والبكتريولوجي لالتهابات المسالك البولية، وتحديد خصائص مقاومة المضادات الحيوية للبكتيريا المعوية المعزولة وتقييم قدرتها على تكوين غشاء حيوي. من بين 200 ECBU، كان معدل انتشار الالتهابات البولية المؤكدة 15.5٪، مع غلبة الإناث (56٪) وأغلبية المرضى في المستشفى (75٪). مثلت البكتيريا المعوية 74% من العزلات، وسيطر عليها الإشريكية القولونية (38.7%) والكلبسيلا الرئوية (29%). أظهر مخطط المضادات الحيوية مقاومة عالية: أمبيسيلين 100%، سيفوتاكسيم 87%، حمض أموكسيسيلين-كلافولانيك وسيبروفلوكساسين حوالي 80%. كشفت الأنماط الظاهرية للمقاومة عن 33% من سلالات و40% من الكاربابينيمات، بما في ذلك خمسة ميتالو بيتا لاكتاماز. كان تكوين الأغشية الحيوية (اللون الأرجواني البلوري) متغيرًا، مع وجود ارتباط كبير بين القسطرة البولية والأغشية الحيوية القوية (ع = 0.007)، ولكن لا يوجد ارتباط مع المقاومة أو الكاربابينيمات. تؤكد هذه النتائج الحاجة الملحة إلى تعزيز المراقبة وترشيد العلاج بالمضادات الحيوية وتطوير استراتيجيات مكافحة الأغشية الحيوية. --------------------------------------------------------------------------------------------------------------------------------------------------------
Keywords: Urinary tract infections; Enterobacteriaceae; Antibiotic resistance; Extendedspectrum beta-lactamases (ESBLs); Biofilm; الالتهابات البولية، البكتيريا المعوية، مقاومة المضادات الحيوية، بيتا لاكتاماز ممتد الطيف (ESBL)، الأغشية الحيوية.; Infections urinaires; Entérobactéries; Résistance aux antibiotiques; Bêtalactamases à spectre étendu (BLSE); Biofilm.